Systematic Literature Review (SLR): Kinerja UMKM di Indonesia dilihat dari Faktor Internal - Ratna Dewi Sari; Noviyanti Alawiyah; Maria Iza; Agus Munandar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Indonesia as a developing country with the largest economic growth rate among the G-20 member countries which continuously strives to improve its economic sector so that it is more developed. Various efforts have been made by the government in realizing economic progress for the welfare of the people, one of which is by creating jobs and equalizing income through sustainable, empowering and people centered economic development through the development of MSMEs (Micro, Small and Medium Enterprises). Despite having a strategic role and receiving support from the government, developing MSME performance is not easy and often faces several obstacles that are dominantly derived from internal factors where MSME organizers have not been able to fully anticipate and overcome business challenges that are dynamic and difficult to compete with other companies. SLR (Systematic Literature Review) method was used in this observation with the aim of analyzing, assessing, and reviewing or reviewing findings that were systematically identified based on previous research evidence regarding internal factors that influence the performance of MSMEs in Indonesia. Research data was obtained from Google Scholar for the 2019-2022 period, based on an initial search, it was found that there were 1,600 articles and only 147 articles were used as data sources and will be examined in more depth. The results of the research found that aspects of human resources include human resource competence, financial understanding or financial literacy, financial knowledge, financial behavior, and entrepreneurial orientation; financial aspects include financial inclusion and financial technology (fintech); operational and technical aspects covering innovation and infrastructure; and market and marketing aspects including marketing strategy, consumers, social media, market orientation, brands, and e-commerce are the dominant internal factors that influence MSMEs in Indonesia.